FWB (Friends With Benefits) and Moral Sexual Consent Problems - Henri Sholahudin; Yongki Sutoyo; Jannatul Firdausi Rahmah (al-Afkar, Journal For Islamic Studies, 2024)
The Friends with Benefits or FWBR phenomenon is now starting to be normalized. Especially among students in big cities in Indonesia. This takes into account that young people in these cities have higher mobility compared to other cities. Furthermore, massive mainstream media coverage regarding FWB experiences was also shared by several public figures. Examining this further, this occurs because several public figures have repeatedly experienced failed committed relationships and want to seek relationship satisfaction in other forms. This supports the rise of the FWB phenomenon among young people. FWB itself is a type of modern sexual relationship or can be said to be a form of casual sexual relationship. This relationship indicates that the phenomenon of having a casual sexual relationship has become something that is known and practiced normally by young people in Indonesia. Fulfilling each other's sexual needs has become The main points in having a FWB relationship. This is in line with the paradigm concept of sexual consent which is the main thing that must be fulfilled in a healthy relationship when having sexual relations. The existence of sexual consent is also an important point in a FWB relationship, which provides legitimacy to obtain "benefits" in the form of sexual relations between both parties which benefit each other. Therefore, this article will examine the causes of the emergence of FWB, its forms, implications. that occurred and tested the claims of its proponents which, if examined further, have many weaknesses.